2020
DOI: 10.1002/adhm.202000818
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanomaterial Engineering for Macrophage‐Mediated Inflammation and Tumor Treatment

Abstract: Macrophages play an important role in the body's immune defense process. Phenotype imbalance between M1 and M2 macrophages induced by inflammation‐related disorders and tumor can also be reversibly converted to treat these diseases. As exogenous substances, a large part of gold‐based nanomaterials interact with macrophages once they enter the body, which provides gold nanomaterials a huge advantage to act as imaging contrasts, active substance carriers, and therapeutic agents for macrophage modulation. By cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 106 publications
0
14
0
Order By: Relevance
“…The inflammation process is a protective response which consists of immune cells, blood vessels, and molecular mediators. 45 The function of inflammation is to eliminate the initial cause of cell injury, clear out necrotic cells and tissues damaged from the original insult and the inflammatory process, and initiate tissue repair. It is reported that structures with nano-scale features possess surface nano-topography and influence inflammatory cell response.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation process is a protective response which consists of immune cells, blood vessels, and molecular mediators. 45 The function of inflammation is to eliminate the initial cause of cell injury, clear out necrotic cells and tissues damaged from the original insult and the inflammatory process, and initiate tissue repair. It is reported that structures with nano-scale features possess surface nano-topography and influence inflammatory cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the upregulated ROS level in the pro-inflammatory cells of the inflammation-related diseases, AuNPs modified with antioxidants have been reported. The functionalized AuNPs can be used as ROS scavenging agents by entering the cells or organisms and exhibit good antioxidative effect . TEMPO and its derivatives are potentially powerful agents for ROS scavenging.…”
Section: Organic Antioxidant Modification For Enhancement Of Ros Scav...mentioning
confidence: 95%
“…And there also had research on imageable nanomaterials in inflammatory and infectious diseases. For example, gold nanomaterials have shown great application potential in macrophage-mediated inflammation imaging and therapy ( Chen W. et al, 2021 ). And MRI-guided sonodynamic therapy has important implications for drug-resistant deep bacterial infections ( Wang D. et al, 2021 ).…”
Section: The Biomedical Applications Of Imageable Nanomaterialsmentioning
confidence: 99%